The Piano Mill: Nostalgic Music and Architecture in the Australian Bush. - Griswold, Erik (Leonardo Music Journal, 2017)
The Piano Mill is a tower in the forest of New South Wales designed and purpose-built to house 16 reclaimed pianos. Architect Bruce Wolfe conceived it as a massive sound sculpture incorporating a steampunk look and nineteenth-century acoustical devices. To launch The Mill the author composed a new work, All's grist that comes to the mill, that responds to the architecture, the natural environment and Australian colonial heritage.